The Factors That Influence Carbon Emission Disclosure In Manufacturing Companies Listed On The Idx For The Period 2020-2022 - Muttaqin, Husnul; Susanti, Susanti; Arimurti, Rizqa (Jurnal Mantik, 2024)
This study aims to investigate the factors that influence the disclosure of carbon emissions in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020-2022. This study focuses on several variables, such as the global reporting initiative (GRI), external auditor reputation, and leverage to determine their influence on the company's decision to disclose carbon emissions. This study uses quantitative methods with the population being all manufacturing companies listed on the IDX. Using purposive sampling method, 63 companies were selected as samples. Data analysis was conducted using multiple regression analysis. The results of this study indicate that GRI and external auditor reputation have a positive influence and leverage has a negative influence on carbon emissions disclosure. These findings support the importance of companies to continuously improve their environmental performance in an effort to reduce the impact of global climate change. The implications of this study are relevant for companies, investors, and policy makers focused on improving sustainability practices in the corporate sector